The Complex Interplay Between Physical Activity and Recovery Styles in Patients With Severe Mental Disorders in a Real-World Multicentric Study - Sampogna, Gaia; Luciano, Mario; Di Vincenzo, Matteo; Andriola, Ileana; D'Ambrosio, Enrico; Amore, Mario; Serafini, Gianluca; Rossi, Alessandro; Carmassi, Claudia; Dell'Osso, Liliana; Di Lorenzo, Giorgio; Siracusano, Alberto; et al. (Frontiers in Psychiatry, 2022)
Compared with the general population, people with severe mental disorders have significantly worse physical health and a higher mortality rate, which is partially due to the adoption of unhealthy lifestyle behaviours, such as heavy smoking, use of alcohol or illicit drugs, unbalanced diet, and physical inactivity. These unhealthy behaviours may also play a significant role in the personal and functional recovery of patients with severe mental disorders, although this relationship has been rarely investigated in methodologically robust studies. In this paper, we aim to: a) describe the levels of physical activity and recovery style in a sample of patients with severe mental disorders; b) identify the clinical, social, and illness-related factors that predict the likelihood of patients performing physical activity. The global sample consists of 401 patients, with a main psychiatric diagnosis of bipolar disorder (43.4%, N=174), psychosis spectrum disorder (29.7%; N=119), or major depression (26.9%; N=118). 29.4% (N=119) of patients reported performing physical activity regularly, most frequently walking (52.1%, N=62), going to the gym (21.8%, N=26), and running (10.9%, N=13). Only 15 patients (3.7%) performed at least 75 minutes of vigorous physical activity per week. 46.8% of patients adopted sealing over as a recovery style and 37.9% used a mixed style towards integration. Recovery style is influenced by gender (p<.05) and age (p<.05). The probability to practice regular physical activity is higher in patients with metabolic syndrome (OR: 2.1; CI 95%: 1.2-3.5; p<.050), and significantly lower in those with higher levels of anxiety/depressive symptoms (OR: 0.877; CI 95%: 0.771 to 0.998; p<.01). Globally, patients with severe mental disorders report low levels of physical activities, which are associated with poor recovery styles. Educational interventions aimed at increasing patients’ motivation to adopt healthy lifestyle behaviours and modify recovery styles may improve the physical health of people with severe mental disorders thus reducing the mortality rates.